2012
DOI: 10.1007/s00431-012-1680-1
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, placebo-controlled trial on the effect of piracetam on breath-holding spells

Abstract: Breath-holding spells (BHS) are apparently frightening events occurring in otherwise healthy children.The aim of this study was to evaluate the efficacy of piracetam in the treatment of breath-holding spells. Forty patients with BHS (who were classified into two groups)were involved in a double-blinded placebo-controlled prospective study. Piracetam was given to group A while group B received placebo. Patients were followed monthly for a total period of 4 months. The numbers of attacks/month before and monthly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 9 publications
1
19
1
1
Order By: Relevance
“…Furthermore, it has been found that cyanotic BHS are more common than pallid BHS. Cyanotic BHS has been reported in 54%-62% of cases, pallid BHS has been reported in 19%-22% of cases, and mixed or unclassifiable BHS has been reported in 19%-24% of cases (18,20).In the present study, 90% of children had cyanotic spells, which was a higher proportion than previously reported.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, it has been found that cyanotic BHS are more common than pallid BHS. Cyanotic BHS has been reported in 54%-62% of cases, pallid BHS has been reported in 19%-22% of cases, and mixed or unclassifiable BHS has been reported in 19%-24% of cases (18,20).In the present study, 90% of children had cyanotic spells, which was a higher proportion than previously reported.…”
Section: Discussioncontrasting
confidence: 58%
“…There have been cases of prolonged asystole with breath holding spells warranting the placement of a permanent cardiac pacemaker [27, 28]. Piracetam has been shown to be safe and effective in treating BHS [29]. In one study, resolution of spells after 2-month therapy with piracetam, was seen in 92% children, compared to 30% resolution in the placebo group [30].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, some studies failed to show the relationship between iron-deficiency anemia and BHS. 3,6,7 Piracetam has been reported to be safe and effective in treating BHS in two case-control studies 8,9 glycopyrrolate, 10 theophylline, 11 and fluoxetine 12 have been considered as alternative agents to treat BHS in individual cases, but efficacy and safety of these treatments still remain to be confirmed by further studies. In some refractory cases, patients were treated with implantation of cardiac pacemaker.…”
Section: Introductionmentioning
confidence: 99%